2011
DOI: 10.1186/1556-276x-6-549
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring photonic metamaterial resonances for thermal radiation

Abstract: Selective solar absorbers generally have limited effectiveness in unconcentrated sunlight, because of reradiation losses over a broad range of wavelengths and angles. However, metamaterials offer the potential to limit radiation exchange to a proscribed range of angles and wavelengths, which has the potential to dramatically boost performance. After globally optimizing one particular class of such designs, we find thermal transfer efficiencies of 78% at temperatures over 1,000°C, with overall system energy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…sensing applications for environmental and medical studies 1,2 to energy harvesting with solar thermophotovoltaics [3][4][5] and infrared emissions from Earth to space 6 . Thermal radiation is also essential to thermal management applications as in microelectronics 7 , space technology 8 and buildings 9 .…”
mentioning
confidence: 99%
“…sensing applications for environmental and medical studies 1,2 to energy harvesting with solar thermophotovoltaics [3][4][5] and infrared emissions from Earth to space 6 . Thermal radiation is also essential to thermal management applications as in microelectronics 7 , space technology 8 and buildings 9 .…”
mentioning
confidence: 99%
“…The property of multilayered structures to exhibit wavelength selectivity can be explained by the presence of surface phonon polaritons (SPhPs) for polar materials and surface plasmon polaritons (SPPs) for metals [5,7]. It has also been demonstrated that two-dimensional (2-D) or three-dimensional (3-D) photonic crystals can be used to develop selective emitters [8,9]. However, thin-film-layered structures are easy to design and fabricate.…”
Section: Introductionmentioning
confidence: 99%
“…Both selective emitters and absorbers made of W have been presented based on this approach. 20,40,41 Based on a 2D array of cylindrical cavities in W, an optimized design for broadband angular and spectral selectivity of a solar absorber was recently presented. 41 Such an absorber operating at 1,000 K and employing 100 sun concentration yields a thermal transfer efficiency of 74.1%.…”
Section: Tungsten Selective Emittersmentioning
confidence: 99%